Reticulascaceae hyphomycetes from submerged wood in Yunnan, China - Maharachchikumbura, Sajeewa S.n.; Luo, Zong-Long; Su, Hong-Yan; Al-Sadi, Abdullah M.; Cheewangkoon, Ratchadawan (Phytotaxa, 2018)
Asexual members of Reticulascaceae (Glomerellales, Hypocreomycetidae) are generally hyphomycetes and usually found as saprobes occurring on various hosts in lentic habitats. A brief survey of the freshwater fungi in Yunnan Province, China, was carried out and four species of Reticulascaceae were isolated. Morphological examination and sequence analysis of large subunit of the nuclear ribosomal RNA (LSU), RNA polymerase II gene encoding the second largest protein subunit (RPB2) and internal transcribed spacer (ITS) regions provide evidence for two taxonomic novelties of Kylindria (K. aquatica and K. chinensis). Two other collections comprised two previously described species of Cylindrotrichum (C. clavatum and C. gorii). Descriptions and illustrations of the above taxa are provided and new species are discussed with comparable taxa.